The Kidney A Comprehensive Guide to Pathologic Diagnosis and Management - Hansel, Donna E.; Kane, Christopher J.; Paner, Gladell P.; Chang, Sam S. (Springer New York : Imprint: Springer, 2016)
This volume provides a practical, comprehensive overview on benign and malignant disease of the adult kidney. The text addresses the topic of assessment and management of patients with surgical renal disease. Within this scope, it includes hereditary and spontaneous renal neoplasms, as well as non-neoplastic disease that manifests as a clinically relevant mass.  The book is organized into chapters focusing on discrete disease entities and incorporating pathology, surgical management, oncologic therapy, radiologic findings, and molecular alterations.  This text is designed to address relevant areas of clinical management of renal neoplastic and non-neoplastic disease across multiple specialties and levels of training.  Written by experts in the field, The Kidney: A Comprehensive Guide to Pathologic Diagnosis and Management is a valuable resource on the diagnosis and management of patients with not only renal cell carcinoma, but also other renal processes that require surgical intervention.     .